Daniel the prophet and the time of the Gentiles - Dennett, Edward, 1831-1914 (Oak Park, IL Bible Truth, 1967)
Includes bibliographical references.
First published 1893. Brethren writer.
Keywords: Bible. O.T. Daniel -- criticism, interpretation, etc